Phenomenological Subjectivity as an Intersection Between Philosophy and Literature - Boshkova, Iskra Tasevska Hadji (Mediterranean Journal of Social Sciences, 2012)
Thorough depiction of the problem of phenomenological subjectivity is a profound, and contemporary challenge. Investigationsof young and late Husserl, as well as his successors (that upgraded the phenomenological project) – Martin Heidegger, RomanIngarden, Jacques Derrida, Roland Barthes, Michel Foucault, etc. should provide us with a large interdisciplinary context, especiallybetween philosophy and literary criticism. The question of subjectivity is something which contemporary epistemology cannot deny – it isdominant aspect in the domains of literary theory (author, narrator, reader), as well as in philosophical inquiries (practical, metaphysical,transcendental subject, etc.). This paper aims to reunite this concept within a wider context – the question of subjectivity is more than19th century, modern, or postmodern product. It concerns the provisional status of subject as existential Sein, but also the possibility toconsider postmodern subjectivity as its confirmation. On the one hand, in Derrida’s terms, solicitation is the movement of self, destructionof totality, but on the other it is also “being “ as presence in the living present, that ultimately is not available for diminution, especiallybecause its uniformity cannot be theoretically grasped.